Artificial intelligence and security challenges in emerging networks - Abassi, Ryma, 1980- (Engineering Science Reference, 2019)
"This book explores the recent rise of emerging networking technologies such as social networks, content centric networks, IoT networks, etc. It also examines the applications of artificial intelligence (AI), machine learning, and data mining to security and privacy problems"--